PERAN DIGITAL MARKETING DALAM PERSPEKTIF EKONOMI ISLAM DI INDONESIA - Sunaryono, Sunaryono (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STIE Pontianak, 2023)
In general, marketing involves a series of activities in the field of trade where sellers offer products to consumers. A similar situation occurs in Islamic marketing, where the process and strategy of meeting needs through halal products and services are accompanied by principles of agreement and mutual well-being between buyers and sellers, with the aim of achieving material and spiritual prosperity in both the worldly life and the hereafter. In the context of digital marketing from an Islamic perspective, all marketing activities that use technology must be based on Sharia law. Therefore, the use of technology should avoid elements involving riba (interest), maisir (gambling), the production or sale of non-halal products, as well as prohibitions related to marketing products containing gharar (uncertainty).